2014
DOI: 10.1080/15367967.2014.945116
|View full text |Cite
|
Sign up to set email alerts
|

Interlibrary Loan Article Use and User GPA: Findings and Implications for Library Services

Abstract: A recent institutional study at the University of Wisconsin-Green Bay investigated the academic achievement of interlibrary loan (ILL) users as compared to non-ILL users. While this study provided important local insight into ILL use and the demographics of ILL users (class rank, major), it uncovered a rather minor overall GPA difference, .20 GPA points, between ILL users and non-ILL users. However, within this data was an interesting subset that once thoroughly investigated, provided rich details about ILL ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In 14.16% of the total. As the data show, the main users are from liberal arts schools, and the demands of users from science schools are relatively low.…”
Section: A Overall Situationmentioning
confidence: 99%
“…In 14.16% of the total. As the data show, the main users are from liberal arts schools, and the demands of users from science schools are relatively low.…”
Section: A Overall Situationmentioning
confidence: 99%
“…A significant number of studies, 46 of the 54 examined, imply transferring individual-level data between the library and a central university office (Allison, 2015;Black & Murphy, 2017;Bowles-Terry, 2012;Çetin & Howard, 2016;Collins & Stone, 2014;Coulter, Clarke, & Scamman, 2007;Cox & Jantti, 2012a, 2012bde Jager et al, 2018;Fransen & Peterson, 2016;Goodall & Pattern, 2011;Haddow, 2013;Haddow & Joseph, 2010;Jantti, 2016;Jantti & Cox, 2013;J. L. Jones, 2010;Kot & Jones, 2015;LeMaistre, 2015;LeMaistre et al, 2018;Massengale, Piotrowski, & Savage, 2016;McCarthy, 2017;Montenegro et al, 2016;Murray et al, 2016;Nackerud et al, 2012Nackerud et al, , 2013Odeh, 2012;Pepper & Jantti, 2015;Renaud et al, 2015;Scarletto et al, 2013;Scott, 2014;Soria et al, 2014Soria et al, , 2017aSoria et al, , 2017bSoria et al, , 2013Soria et al, , 2015Squibb & Mikkelsen, 2016;Stemmer & Mahan, 2015Stone, Pattern, & Ramsden, 2012;Thorpe et al, 2016;…”
Section: Securitymentioning
confidence: 99%
“…Most libraries characterize resource usage as either the student "did use" or "didn't use" that resource type during the study or group usage into several frequency levels. However, eight studies counted the total number of transactions in a specific category (Allison, 2015;Çetin & Howard, 2016;Collins & Stone, 2014;LeMaistre et al, 2018;Montenegro et al, 2016;Scott, 2014;Thorpe et al, 2016). This method is touted as a way to protect patron privacy when it may not, in fact, truly do so.…”
Section: Anonymizationmentioning
confidence: 99%
“…Four grade studies did not provide enough information in the published report to calculate an effect size (Davidson et al 2013;deJager 2002;Moore et al 2002;Scott 2014). Three grade studies (Chodock 2018;Stemmer & Mahan 2016;Wells 1995) and one retention study (Stemmer & Mahan 2016) were excluded due to self-reported independent variables in their research design.…”
Section: Gradementioning
confidence: 99%